2015
DOI: 10.3109/14767058.2015.1064886
|View full text |Cite
|
Sign up to set email alerts
|

The cellular immunity and oxidative stress markers in early pregnancy loss

Abstract: We have demonstrated an increased cellular immunity and perhaps a compensated oxidative stress related to increased antioxidant activation in women with early spontaneous pregnancy loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A recent study has demonstrated a link between compensated oxidative stress and spontaneous abortion in women with early spontaneous pregnancy loss compared to normal women with ongoing pregnancy. 15…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated a link between compensated oxidative stress and spontaneous abortion in women with early spontaneous pregnancy loss compared to normal women with ongoing pregnancy. 15…”
Section: Discussionmentioning
confidence: 99%
“…BPA toxicity on female reproduction also involves the occurrence of endometriosis, miscarriage, and abnormalities of uterus morphology [94]. The common thread among these disorders is the increased oxidative stress [126], along with the activation of inflammatory signaling. Indeed, Cho et al [22] have demonstrated the capability of BPA to induce oxidative stress and inflammatory mediators in human endometrial cells.…”
Section: Oxidative Stress-induced Bpa Toxicity On Male and Female Rep...mentioning
confidence: 99%
“…Over the years, infertility related to OS has become an area of great concern for clinicians and scientists because continuous formation of ROS throughout the life of an organism leads to cumulative damage, which impairs fertility via programmed deterioration. The deleterious consequences of OS include impairment of semen parameters (Agarwal et al, 2005;Bansal and Bilaspuri, 2010;Pasqualotto et al, 2000), poor fertilization, poor embryonic development (Jana et al, 2010;Oyawoye et al, 2003) and pregnancy loss (Cengiz et al, 2016;Daglar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%